PEMANFAATAN CUKA KAYU GALAM (Melaleuca sp.) DENGAN BERBAGAI PERLAKUAN SEBAGAI PENGAWET ALAMI TELUR ASIN - Nurmilatina, Nurmilatina (Kementerian Perindustrian, 2015)
Melaleuca sp. very abundant in South Kalimantan and mostly used as firewood. Utilization of wood vinegar now it has expanded, including as a food preservative. This is because it contains with phenolic compounds, carbonyl and acid compounds which useful as antimicrobial, antioxidant, forming smell, flavor and color. This study purpose to know influence of concentration and soaking time wood vinegar of Melaleuca sp on organoleptic and microbiological salted eggs. This research used randomized block design with two factors, that is concentration of wood vinegar and soaking time. The best result based on the parameters accordance with SNI 01-2891-1992 about salted egg, obtained in 3 weeks storage at room temperature with a 10% concentration ofand soaking time 1 hour. Results obtained by the value of flavor is 4.00; color 3.90; appearance 3.90; salt 4,500%; negative Salmonella and Staphyloccocus 0 colonies g.Keywords: wood vinegar, Melaleuca Cajuput, food preservative, salted eggs